1973
DOI: 10.1002/aic.690190404
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in high viscosity liquids

Abstract: The diffusion coefficients D of n‐hexane and of naphthalene in a series of hydrocarbon liquids with viscosities μ from 5 · 10−4 to 5 kg m−1 sec−1 (0.5 to 5000 centipoise) have been measured at 25°C with a one Savart plate wavefront‐shearing interferometer. This apparatus allows direct determinations at effectively infinite dilution. The values obtained suggest that for a small solute diffusing in a large solvent a result consistent with earlier studies. The exponent of 2/3 may be rationalized on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(71 citation statements)
references
References 24 publications
4
67
0
Order By: Relevance
“…This characteristic parameter would be directly related to the strength of interaction of diffusing species with its environment; the higher the value of α the lesser the interaction. Indeed, it has been found that α tends to 1 when the solute/solvent size ratio is greater than 5, and to 0 in extremely highly viscosity media [73]. Furthermore, α has been found to equal to 1 for water in hydrophobic media [71].…”
Section: H Nmr Dosymentioning
confidence: 99%
“…This characteristic parameter would be directly related to the strength of interaction of diffusing species with its environment; the higher the value of α the lesser the interaction. Indeed, it has been found that α tends to 1 when the solute/solvent size ratio is greater than 5, and to 0 in extremely highly viscosity media [73]. Furthermore, α has been found to equal to 1 for water in hydrophobic media [71].…”
Section: H Nmr Dosymentioning
confidence: 99%
“…As in the case of strongly viscous liquids, the anomalies arise upon diffusion of small admixtures [45,46]. The diffusion of various admixtures in 2-methylpentane-2,4-diol has been studied in [47].…”
Section: Determination Of Diffusion Rate Constant Using Reaction Of Dmentioning
confidence: 99%
“…The enhanced diffusion has been explained by the so-called microviscosity effect, i.e., the viscosity around a small solute is different from the bulk viscosity of solvent. 67 Although Hiss and Cussler 58 have been able to rationalize the exponent of 2/3 on the basis of Eyring's absolute rate theory and Bagchi and Bhattacharyya 7,19 have indicated in their MCT studies that decoupling of the solute motion from the structural relaxation of the solvent could lead to fractional viscosity dependence, nonetheless, a quantitative theory of the FSE relation is still not yet available. Recently, however, there has been a great deal of interest [68][69][70][71][72][73][74][75][76] in the use of the FSE relation for the study of diffusion.…”
Section: B Solvent Dependencementioning
confidence: 99%
“…Except for macromolecules, however, numerous experimental studies 3,[57][58][59][60][61][62][63][64][65][66] have shown that tracer diffusivity is inversely proportional to a fractional power of the viscosity of the solvent instead. This fractional power dependence of viscosity on diffusion is often referred to in the literature as the fractional Stokes-Einstein (FSE) relation, (D 12 /T) ∝ η −t , where t is known to be normally less than unity and generally around 2/3.…”
Section: B Solvent Dependencementioning
confidence: 99%
See 1 more Smart Citation